Assessing the role and effectiveness of audit committees in some selected rural banks in Ghana - Osei, Evans Bonsu (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Accounting Option)